apo B gene knockout in mice results in embryonic lethality in homozygotes and neural tube defects, male infertility, and reduced HDL cholesterol ester and apo A-I transport rates in heterozygotes. - Huang, L S (1995)
apo B is a structural constituent of several classes of lipoprotein particles, including chylomicrons, VLDL, and LDL. To better understand the role of apo B in the body, we have used gene targeting in embryonic stem cells to create a null apo B allele in the mouse. Homozygous apo B deficiency led to embryonic lethality, with resorption of all embryos by gestational day 9. Heterozygotes showed an increased tendency to intrauterine death with some fetuses having incomplete neural tube closure and some live-born heterozygotes developing hydrocephalus. The majority of male heterozygotes were sterile, although the genitourinary system and sperm were grossly normal. Viable heterozygotes had normal triglycerides, but total, LDL, and HDL cholesterol levels were decreased by 37, 37, and 39%, respectively. Hepatic and intestinal apo B mRNA levels were decreased in heterozygotes, presumably contributing to the decreased LDL levels through decreased synthesis of apo B-containing lipoproteins. Kinetic studies indicated that heterozygotes had decreased transport rates of HDL cholesterol ester and apo A-I. As liver and intestinal apo A-I mRNA levels were unchanged, the mechanism for decreased apo A-I transport must be posttranscriptional. Heterozygotes also had normal cholesterol absorption and a normal response of the plasma lipoprotein pattern to chronic consumption of a high fat, high cholesterol, Western-type diet. In summary, we report a mouse model for apo B deficiency with several phenotypic features that were unexpected based on clinical studies of apo B-deficient humans, such as embryonic lethality in homozygotes and neural tube closure defects, male infertility, and a major defect in HDL production in heterozygotes. This model presents an opportunity to study the mechanisms underlying these phenotypic changes.